Kottelatlimia hipporhynchos, a new species of loach from southern Borneo (Teleostei: Cobitidae) - Kottelat, Maurice; Tan, Heok Hui (Zootaxa, 2008)
Kottelatlimia hipporhynchos, new species, is described from the Sampit, Kahayan and Kapuas drainages, southern Borneo. It is distinguished from its congeners by the extreme development of the papillae on all mouth parts (lips, barbels, lobes), including very long papillae along the anterior edge of the main digitation of the median lobe of the lower lip; a longer snout; more vertebrae; and the upper 3–4 principal caudal-fin rays adjacent along proximal 1/4–1/3. Sexual dimorphism of the pectoral fin of Acantopsis and Neoeucirrhichthys is briefly discussed. The identity and nomenclatural status of Cobitis barbatuloides and Cobitichthys are discussed; they apparently belong to the genus Lepidocephalichthys, which is given precedence under article 23.9.2 of the International Code of Zoological Nomenclature.